Agshare Open Knowledge: Improving Rural Communities through University Student Action Research - Geith, Christine; Vignare, Karen (Online Learning, 2013)
The aim of AgShare is to create a scalable and sustainable collaboration of existing organizations for African publishing, localizing, and sharing of science-based teaching and learning materials that fill critical resource gaps in African MSc agriculture curriculum. Shared innovative practices are emerging through the AgShare projects, not only for creating and sharing Open Educational Resources (OER), but also for collaborating with stakeholders and with students to bridge the gap between theory and local practice in African university agriculture curriculum.